Physicochemical characteristics of some locally manufactured edible vegetable oils marketed in Dar es Salaam - Ngassapa, F N; Othman, O C (Tanzania Journal of Science, 2021)
The physicochemical properties (refractive index, saponification value, Free Fatty Acid (FFA) value, iodine value, acid value, peroxide value and tocopherol content) of seven edible vegetable oils manufactured in Tanzania, were assessed using standard procedures of the Association of Official Analytical Chemists (AOAC). Also determined were the levels of these properties with respect to shelf storage of the products. When compared with standard values recommended by the Codex Alimentarius Commission of FAO/WHO and with other published results, the locally produced vegetable oils were found to be of fair quality but of poor storage stability.